Handbook of Injury and Violence Prevention - Doll, Lynda S.; Bonzo, Sandra E.; Sleet, David A.; Mercy, James A.; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Injuries kill and maim millions each year, and seriously impact the lives of countless loved ones. Yet until recently they$1 (Bve been considered a random, normal part of life. Preventing injuries, on the other hand, requires not only effective communication with the public, but also a reliable framework for creating and evaluating suitable interventions. The Handbook of Injury and Violence Prevention is the first book to address both halves of this challenge, reviewing evidence-based intervention programs in depth so professionals can identify successful, promising, and ineffective (and potentially harmful) prevention strategies. Over fifty experts present the current landscape of intervention methods - from risk reduction to rethinking social norms - as they address some of the most prevalent forms of accidental and violent injury, as well as emerging areas. - Overview chapters examine the social and economic scope of unintentional and violent injury today - Extensive literature review of specific intervention programs to prevent violence and injury - Special chapters on childhood injuries, alcohol-related accidents, and disasters - "Interventions in the Field" section offers solid guidelines for implementing and improving existing programs - Critical analysis of issues involved in delivering programs to wider audiences - Helpful appendices list relevant agencies and professional resources This dual focus on intervention and application makes the Handbook a bedrock text for professionals involved in delivering or managing prevention programs. Its what-works-now approach gives it particular utility in the graduate classroom, and researchers will benefit from the critical attention paid to knowledge gaps in the field. It is a major resource for any reader committed to reducing the number of incidents just waiting to happen.s
The Epidemiology and Costs of Unintentional and Violent Injuries -- Injury and Violence Prevention Interventions: An Overview -- Effective and Promising Interventions -- Interventions to Prevent Falls Among Older Adults -- Interventions to Prevent Motor Vehicle Injuries -- Interventions to Prevent Drowning -- Interventions to Prevent Residential Fire Injury -- Interventions to Prevent Sports and Recreation-Related Injuries -- Interventions to Prevent Child Maltreatment -- Interventions to Prevent Youth Violence -- Interventions to Prevent Suicidal Behavior -- Interventions to Prevent Intimate Partner Violence -- Interventions to Prevent Sexual Violence -- Interventions to Prevent Elder Mistreatment -- Cross-Cutting Intervention Issues -- Changing the Built Environment to Prevent Injury -- Changing the Social Environment to Prevent Injuries -- Interventions to Prevent Alcohol-Related Injuries -- Reducing the Misuse of Firearms -- Parenting and the Prevention of Childhood Injuries -- Building Resilience to Mass Trauma Events -- Trends and Challenges in Intervention Research Methods -- Interventions in the Field -- Interpreting Evidence of Effectiveness: How Do You Know When a Prevention Approach Will Work for Your Community? -- Behavioral Interventions for Injury and Violence Prevention -- Developing Interventions When There Is Little Science -- Developing and Implementing Communication Messages -- Cultural Appropriateness in Interventions for Racial and Ethnic Minorities -- Evaluating Fidelity and Effectiveness of Interventions -- Involving the Community in Injury Prevention: An Approach Using Community Readiness Interviews -- Dissemination and Adoption of Effective Interventions and Policies -- Dissemination, Implementation, and Widespread Use of Injury Prevention Interventions -- Encouraging Adoption of Science-Based Interventions: Organizational and Community Issues -- Erratum.
Keywords: Medicine; Public health; Health promotion; Epidemiology; Medicine & Public Health; Public Health; Health Promotion and Disease Prevention; Epidemiology; Electronic books